DIGITAL STORYTELLING OF â€œMICROSOFT PHOTO STORY 3 FOR WINDOWSâ€ TO IMPROVE THE INVOLVEMENT OF STUDENTS IN THE PROCESS OF LEARNING ENGLISH IN THE CLASSROOM - Effendi Limbong (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: The use of technology effectively in the teaching and learning process is essential skills for teachers to help them make a complex subject simples for students while students themselves need more strategies and variation from teachers to help them to absorb every information more easily, particularly when learning the English language. The students are now living in the technology era, which means modern technological tools are around them constantly updated and very competitive. Thus, teachers as the main actors who have the responsibility to transfer knowledge to students must prepare themselves with technological skills. Without these skills, teachersâ€Ÿ pedagogical knowledge and content knowledge for undertaking their daily activities in teaching will face serious problems in transferring any kinds of knowledge to students. In this paper, I would like to explain the Microsoft Photo Story 3 for Windows in my teaching context at the undergraduate level, particularly its benefits, and the obstacles and challenges in teaching English as a second language in Indonesia.Keywords: technology, Microsoft photo story, teaching and learning English